Matrix Variate Distributions - Gupta, A. K.; Nagar, D. K. (Boca Raton : Chapman and Hall/CRC, 2018)
Useful in physics, economics, psychology, and other fields, random matrices play an important role in the study of multivariate statistical methods. Until now, however, most of the material on random matrices could only be found scattered in various statistical journals. Matrix Variate Distributions gathers and systematically presents most of the recent developments in continuous matrix variate distribution theory and includes new results.After a review of the essential background material, the authors investigate the range of matrix variate distributions, including:matrix variate normal distributionWishart distributionMatrix variate t-distributionMatrix variate beta distributionF-distributionMatrix variate Dirichlet distributionMatrix quadratic formsWith its inclusion of new results, Matrix Variate Distributions promises to stimulate further research and help advance the field of multivariate statistical analysis.
8.5. GENERALIZED BINGHAM-VON MISES MATRIX DISTRIBUTION8.6. MANIFOLD NORMAL DISTRIBUTION; 8.7. MATRIX ANGULAR CENTRAL GAUSSIAN DISTRIBUTION; 8.8. BIMATRIX WISHART DISTRIBUTION; 8.9. BETA-WISHART DISTRIBUTION; 8.10. CONFLUENT HYPERGEOMETRIC FUNCTION KIND 1 DISTRIBUTION; 8.11. CONFLUENT HYPERGEOMETRIC FUNCTION KIND 2 DISTRIBUTION; 8.12. HYPERGEOMETRIC FUNCTION DISTRIBUTIONS; 8.13. GENERALIZED HYPERGEOMETRIC FUNCTION DISTRIBUTIONS; 8.14. COMPLEX MATRIX VARIATE DISTRIBUTIONS; PROBLEMS; 9: GENERAL FAMILIES OF MATRIX VARIATE DISTRIBUTIONS; 9.1. INTRODUCTION
Description based upon print version of record.
9.2. MATRIX VARIATE LIOUVILLE DISTRIBUTIONS
OCLC-licensed vendor bibliographic record.
Keywords: MATHEMATICS / Applied; MATHEMATICS / Probability & Statistics / General